Identifikasi Potensi Wisata Budaya di Kabupaten Minahasa Utara - Mahdalena Heltin Salele; Nixon Jefres Sindua; Jelly Robot; Fonny Rewah (Fakultas Ilmu Sosial dan Hukum, 2023)
The purpose of this study is to determine the potential for cultural tourism in the North Minahasa district. The research method is quantitative, with scoring. The findings show that the historical value of the Waruga tomb and the legendary story of Kolam Tumatenden are categorized as attractive for cultural tourism. The meaning of Waruga is the origin, family lineage, and ancestral struggle. The story of the Tumantenden Pond contains values that we can learn from each of these stories.